Preface: Special issue on the Eleventh International Symposium on Networking and Computing - Nakano, Koji (International Journal of Networking and Computing, 2024)
The Eleventh International Symposium on Networking and Computing (CANDAR 2023) was held from November 28th to December 1st, 2023. The organizers of CANDAR 2023 invited authors to submit extended versions of the papers presented at the symposium. Out of these submissions, eight papers have been accepted and are included in this issue as extended versions.This issue owes its success to the dedicated efforts and expertise of numerous individuals who generously contributed their time and knowledge in handling the submitted papers. We extend our heartfelt gratitude to the guest editors for their exceptional work in conducting the review process. Special thanks go to: Professor Shoichi Hirasawa, Professor Junya Nakamura, Professor Toru Nakanishi, Professor Yasuyuki Nogami, Professor Tomoyuki Ohta, Professor Hiroyuki Sato, Professor Takashi Yokota. Their valuable contributions ensured the quality and rigor of the review process, making this issue possible.We would also like to express our sincere appreciation to the anonymous reviewers who diligently reviewed the papers and provided insightful comments and suggestions to enhance the quality of the submissions. Their thorough and thoughtful evaluation played a vital role in shaping the content of this special issue. We are truly grateful for their invaluable contributions, as this issue would not have been possible without their dedicated efforts.In conclusion, we are immensely grateful for the collective efforts of all individuals involved in making this special issue a reality. From the organizers, guest editors, and anonymous reviewers, each person has contributed significantly. Their dedication and support have enabled us to present this collection of extended papers, showcasing advancements in networking and computing. We hope this issue inspires further innovation in the field and serves as a valuable resource for researchers and practitioners.